Senam Diabetik Menurunkan Kadar Gula Darah Wanita Usia Dewasa Tengah - Aniek Puspitosari; Ninik Nurhidayah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
The trend of diabetes does not only affect the old age group, but has shifted to the young and productive age group. As a result of this shift, more and more women of childbearing age have diabetes. Until now, 2 out of 5 women of reproductive age suffer from diabetes, with the number reaching more than 60 million women worldwide. Objective: To determine the effect of diabetic exercise on blood sugar levels in middle-aged women. Methods: Quantitative with a pre-experimental design type one group pretest-posttest. 28 samples were taken using the sampling technique, namely purposive sampling. Data collection with the Glucometer instrument. Result: Shows that the value of p = 0.000 (p<0.05). Conclusion: there is an effect of diabetic exercise on blood sugar levels in middle-aged women.